Preparation process of high-strength magnesia carbon brick
The high-strength magnesia carbon brick preparation process addresses low structural strength by using specific raw material proportions and rigorous inspections, enhancing strength and corrosion resistance.
Patent Information
- Application Number
- CN202411215626.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-02
- Publication Date
- 2024-12-17
AI Technical Summary
Existing magnesia carbon brick preparation processes result in low structural strength due to simple compositions and lack of comprehensive inspection, leading to high maintenance costs for intelligent instruments.
A high-strength magnesia carbon brick preparation process involving specific proportions and grinding of raw materials, followed by molding, baking, and rigorous quality inspections including hardness, corrosion, and fire resistance tests.
Enhances the structural strength, corrosion resistance, and hardness of magnesia carbon bricks, improving their stability and safety through the use of silicon carbide, alumina, graphite, fly ash, and quartz powder, and efficient corrosion resistance detection.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of magnesia carbon brick preparation, in particular to a high-strength magnesia carbon brick preparation process. Background Art
[0002] Magnesia carbon bricks are non-burning carbon composite refractory materials made of high melting point basic oxide magnesium oxide (melting point 2800℃) and high melting point carbon material that is difficult to be wetted by slag as raw materials, adding various non-oxide additives and combining them with carbonaceous binders.
[0003] The magnesia carbon brick preparation process on the market has fewer inspection items after the magnesia carbon brick is formed, and most of the inspections are carried out by intelligent instruments. There are many intelligent instruments, and the cost of subsequent maintenance of the machines is high. In addition, the prepared magnesia carbon bricks are composed of simple components such as magnesium powder, magnesium particles, and graphite, which leads to the problem of low structural strength after forming. For this reason, we propose a high-strength magnesia carbon brick preparation process. Summary of the invention
[0004] The purpose of the present invention is to provide a high-strength magnesia-carbon brick preparation process to solve the problems raised in the above background technology.
[0005] To achieve the above object, the present invention provides the following technical solution: a high-strength magnesia-carbon brick preparation process, the manufacturing process of the high-strength magnesia-carbon brick preparation process has the following steps:
[0006] (1) Proportioning raw materials: Proportioning magnesia particles, flaky graphite, phenolic resin, antioxidant, silicon carbide, alumina, graphite, fly ash, quartz powder, and clay;
[0007] (2) Processing raw materials: grinding the raw materials into particles of the same size and mixing them;
[0008] (3) Molding and baking: Molding and baking the mixed raw materials;
[0009] (4) Final inspection: quality inspection of finished magnesia carbon bricks;
[0010] Preferably, the raw materials are ground into particles of the same size: flaky graphite, silicon carbide, aluminum oxide, graphite, fly ash and quartz powder are ground into 120 meshes by a grinder.
[0011] Preferably, 50 parts of magnesia particles, 10 parts of flaky graphite, 3 parts of phenolic resin, 5 parts of antioxidant, 5 parts of silicon carbide, 2 parts of alumina, 5 parts of graphite, 3 parts of fly ash, 8 parts of quartz powder and 9 parts of clay are mixed and stirred in a mixer at 150-300 rpm for 20-45 minutes.
[0012] Preferably, the molding and baking is as follows: the mixed magnesia carbon brick raw materials are pressed into a mold, and then a 1200-ton refractory brick molding hydraulic press is used to press it 10-20 times at 115-200 MPa to form it. The formed magnesia carbon bricks are sent to a kiln for baking and sintering to obtain finished magnesia carbon bricks.
[0013] Preferably, the final test includes a magnesia carbon brick hardness test, a corrosion resistance test, and a fire resistance test.
[0014] Preferably, the final test samples are 2 samples taken for every 100 finished products for testing:
[0015] (1) Hardness test: Use Rockwell hardness tester to test the hardness of the formed magnesia carbon bricks;
[0016] (2) Corrosion resistance test: Use a pool with a length of 4-7 meters, a width of 2-5 meters, and a height of 1-3 meters. Divide the pool into two equal parts. Fill one of the pools with salt spray test liquid and the other with citric acid solution. Divide the finished magnesia carbon brick samples into two equal parts, place them in the salt spray test liquid for 8-15 hours, and place them in the citric acid solution for 5-10 hours.
[0017] (3) Fire resistance test: Place the finished magnesia carbon bricks in a drying furnace at 1500-2000℃ for 30-260 minutes.
[0018] Preferably, the final inspection is as follows: the magnesia carbon brick product after inspection is fine-finished by a cutting machine and a grinder to obtain a final magnesia carbon brick.
[0019] Compared with the prior art, the present invention has the following beneficial effects:
[0020] 1. The raw materials used in the high-strength magnesia carbon brick preparation process contain silicon carbide, alumina, graphite, fly ash, and quartz powder, which are used to improve the strength of magnesia carbon bricks, increase the corrosion resistance and hardness of magnesia carbon bricks, and make magnesia carbon bricks safer and more stable in subsequent use;
[0021] 2. The high-strength magnesia carbon brick preparation process uses a water pool with an inner cavity divided into two. Two corrosion resistance detection liquids are stored in the two cavities respectively, which are used to classify and detect the corrosion resistance of magnesia carbon bricks and improve the efficiency of corrosion resistance detection. DETAILED DESCRIPTION
[0022] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0023] The present invention provides a technical solution: a high-strength magnesia-carbon brick preparation process, the manufacturing process of the high-strength magnesia-carbon brick preparation process has the following steps:
[0024] (1) Proportioning raw materials: Proportioning magnesia particles, flaky graphite, phenolic resin, antioxidant, silicon carbide, alumina, graphite, fly ash, quartz powder, and clay;
[0025] (2) Processing raw materials: grinding the raw materials into particles of the same size and mixing them;
[0026] (3) Molding and baking: Molding and baking the mixed raw materials;
[0027] (4) Final inspection: quality inspection of finished magnesia carbon bricks;
[0028] Preferably, the raw materials are ground into particles of the same size: flaky graphite, silicon carbide, aluminum oxide, graphite, fly ash and quartz powder are ground into 120 meshes by a grinder.
[0029] Preferably, 50 parts of magnesia particles, 10 parts of flaky graphite, 3 parts of phenolic resin, 5 parts of antioxidant, 5 parts of silicon carbide, 2 parts of alumina, 5 parts of graphite, 3 parts of fly ash, 8 parts of quartz powder and 9 parts of clay are mixed and stirred in a mixer at 150-300 rpm for 20-45 minutes.
[0030] Preferably, the molding and baking is as follows: the mixed magnesia carbon brick raw materials are pressed into a mold, and then a 1200-ton refractory brick molding hydraulic press is used to press it 10-20 times at 115-200 MPa to form it. The formed magnesia carbon bricks are sent to a kiln for baking and sintering to obtain finished magnesia carbon bricks.
[0031] Preferably, the final test includes a magnesia carbon brick hardness test, a corrosion resistance test, and a fire resistance test.
[0032] Preferably, the final test samples are 2 samples taken for every 100 finished products for testing:
[0033] (1) Hardness test: Use Rockwell hardness tester to test the hardness of the formed magnesia carbon bricks;
[0034] (2) Corrosion resistance test: Use a pool with a length of 4-7 meters, a width of 2-5 meters, and a height of 1-3 meters. Divide the pool into two equal parts. Fill one of the pools with salt spray test liquid and the other with citric acid solution. Divide the finished magnesia carbon brick samples into two equal parts, place them in the salt spray test liquid for 8-15 hours, and place them in the citric acid solution for 5-10 hours.
[0035] (3) Fire resistance test: Place the finished magnesia carbon bricks in a drying furnace at 1500-2000℃ for 30-260 minutes.
[0036] Preferably, the final inspection: the magnesia carbon brick product after the inspection is fine-tuned by a cutting machine and a grinder to obtain a final magnesia carbon brick;
[0037] Example 2:
[0038] A high-strength magnesia-carbon brick preparation process, the steps of the high-strength magnesia-carbon brick preparation process are as follows:
[0039] (1) Proportioning raw materials: Proportioning magnesia particles, flaky graphite, phenolic resin, antioxidant, silicon carbide, alumina, graphite, fly ash, quartz powder, and clay;
[0040] (2) Processing raw materials: grinding the raw materials into particles of the same size and mixing them;
[0041] (3) Molding and baking: Molding and baking the mixed raw materials;
[0042] (4) Final inspection: quality inspection of finished magnesia carbon bricks;
[0043] Preferably, the raw materials are ground into particles of the same size: flaky graphite, silicon carbide, aluminum oxide, graphite, fly ash and quartz powder are ground into 120 meshes by a grinder.
[0044] Preferably, 50 parts of magnesia particles, 10 parts of flaky graphite, 3 parts of phenolic resin, 5 parts of antioxidant, 5 parts of silicon carbide, 2 parts of alumina, 5 parts of graphite, 3 parts of fly ash, 8 parts of quartz powder and 9 parts of clay are mixed and stirred in a mixer at 200-300 rpm for 30-45 minutes.
[0045] Preferably, the molding and baking is as follows: the mixed magnesia carbon brick raw materials are pressed into a mold, and then a 1200-ton refractory brick molding hydraulic press is used to press it 16-20 times at 120-160 MPa to form it. The formed magnesia carbon bricks are sent to a kiln for baking and sintering to obtain finished magnesia carbon bricks.
[0046] Preferably, the final test includes a magnesia carbon brick hardness test, a corrosion resistance test, and a fire resistance test.
[0047] Preferably, the final test samples are 2 samples taken for every 100 finished products for testing:
[0048] (1) Hardness test: Use Rockwell hardness tester to test the hardness of the formed magnesia carbon bricks;
[0049] (2) Corrosion resistance test: Use a water pool with a length of 4-6 meters, a width of 2-4 meters, and a height of 1-2 meters. Divide the water pool into two equal parts. Fill one of the water pools with salt spray test liquid and the other with citric acid solution. Divide the finished magnesia carbon brick samples into two equal parts, place them in the salt spray test liquid for 10-15 hours, and place them in the citric acid solution for 6-8 hours.
[0050] (3) Fire resistance test: Place the finished magnesia carbon bricks in a drying furnace and dry them at 1600-1800℃ for 50-220 minutes.
[0051] Preferably, the final inspection: the magnesia carbon brick product after the inspection is fine-tuned by a cutting machine and a grinder to obtain a final magnesia carbon brick;
[0052] Example 3:
[0053] A high-strength magnesia-carbon brick preparation process, the steps of the high-strength magnesia-carbon brick preparation process are as follows:
[0054] (1) Proportioning raw materials: Proportioning magnesia particles, flaky graphite, phenolic resin, antioxidant, silicon carbide, alumina, graphite, fly ash, quartz powder, and clay;
[0055] (2) Processing raw materials: grinding the raw materials into particles of the same size and mixing them;
[0056] (3) Molding and baking: Molding and baking the mixed raw materials;
[0057] (4) Final inspection: quality inspection of finished magnesia carbon bricks;
[0058] Preferably, the raw materials are ground into particles of the same size: flaky graphite, silicon carbide, aluminum oxide, graphite, fly ash and quartz powder are ground into 120 meshes by a grinder.
[0059] Preferably, 50 parts of magnesia particles, 10 parts of flaky graphite, 3 parts of phenolic resin, 5 parts of antioxidant, 5 parts of silicon carbide, 2 parts of alumina, 5 parts of graphite, 3 parts of fly ash, 8 parts of quartz powder and 9 parts of clay are mixed and stirred in a mixer at 220-280 rpm for 35-45 minutes.
[0060] Preferably, the molding and baking is as follows: the mixed magnesia carbon brick raw materials are pressed into a mold, and then a 1200-ton refractory brick molding hydraulic press is used to press it 18-20 times at 130-150 MPa to form it. The formed magnesia carbon bricks are sent to a kiln for baking and sintering to obtain finished magnesia carbon bricks.
[0061] Preferably, the final test includes a magnesia carbon brick hardness test, a corrosion resistance test, and a fire resistance test.
[0062] Preferably, the final test samples are 2 samples taken for every 100 finished products for testing:
[0063] (1) Hardness test: Use Rockwell hardness tester to test the hardness of the formed magnesia carbon bricks;
[0064] (2) Corrosion resistance test: Use a water pool with a length of 5-6 meters, a width of 2-3 meters, and a height of 1-2 meters. Divide the water pool into two equal parts. Fill one of the water pools with salt spray test liquid and the other with citric acid solution. Divide the finished magnesia carbon brick samples into two equal parts, place them in the salt spray test liquid for 12-15 hours, and place them in the citric acid solution for 6-8 hours.
[0065] (3) Fire resistance test: Place the finished magnesia carbon bricks in a drying furnace at 1700-1800℃ for 90-220 minutes.
[0066] Preferably, the final inspection: the magnesia carbon brick product after the inspection is fine-tuned by a cutting machine and a grinder to obtain a final magnesia carbon brick;
[0067] Example 4:
[0068] A high-strength magnesia-carbon brick preparation process, the steps of the high-strength magnesia-carbon brick preparation process are as follows:
[0069] (1) Proportioning raw materials: Proportioning magnesia particles, flaky graphite, phenolic resin, antioxidant, silicon carbide, alumina, graphite, fly ash, quartz powder, and clay;
[0070] (2) Processing raw materials: grinding the raw materials into particles of the same size and mixing them;
[0071] (3) Molding and baking: Molding and baking the mixed raw materials;
[0072] (4) Final inspection: quality inspection of finished magnesia carbon bricks;
[0073] Preferably, the raw materials are ground into particles of the same size: flaky graphite, silicon carbide, aluminum oxide, graphite, fly ash and quartz powder are ground into 120 meshes by a grinder.
[0074] Preferably, 50 parts of magnesia particles, 10 parts of flaky graphite, 3 parts of phenolic resin, 5 parts of antioxidant, 5 parts of silicon carbide, 2 parts of alumina, 5 parts of graphite, 3 parts of fly ash, 8 parts of quartz powder and 9 parts of clay are mixed and stirred in a mixer at 230 revolutions per minute for 40 minutes.
[0075] Preferably, the molding and baking is as follows: the mixed magnesia carbon brick raw materials are pressed into a mold, and then a 1200-ton refractory brick molding hydraulic press is used to press it 20 times at 140MPa to form it. The formed magnesia carbon bricks are sent to a kiln for baking and sintering to obtain finished magnesia carbon bricks.
[0076] Preferably, the final test includes a magnesia carbon brick hardness test, a corrosion resistance test, and a fire resistance test.
[0077] Preferably, the final test samples are 2 samples taken for every 100 finished products for testing:
[0078] (1) Hardness test: Use Rockwell hardness tester to test the hardness of the formed magnesia carbon bricks;
[0079] (2) Corrosion resistance test: Use a water pool with a length of 5 meters, a width of 3 meters, and a height of 1 meter. Divide the water pool into two equal parts. Fill one of the water pools with salt spray test liquid, and the other with citric acid solution. Divide the finished magnesia carbon brick samples into two equal parts, place them in the salt spray test liquid for 12-15 hours, and place them in the citric acid solution for 7 hours.
[0080] (3) Fire resistance test: Place the finished magnesia carbon bricks in a drying furnace and dry them at 1800°C for 150 minutes.
[0081] Preferably, the final inspection is as follows: the magnesia carbon brick product after inspection is fine-finished by a cutting machine and a grinder to obtain a final magnesia carbon brick.
[0082] Working principle: For this type of high-strength magnesia-carbon brick preparation process, the raw materials used contain silicon carbide, alumina, graphite, fly ash, and quartz powder, which are used to improve the strength of magnesia-carbon bricks, increase the corrosion resistance and hardness of magnesia-carbon bricks, and make the magnesia-carbon bricks safer and more stable in subsequent use. The inner cavity of the water pool is divided into two, and two corrosion resistance detection liquids are stored in the two cavities respectively, which are used to classify and detect the corrosion resistance of magnesia-carbon bricks and improve the efficiency of corrosion resistance detection. In this way, the entire high-strength magnesia-carbon brick preparation process is completed.
[0083] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is limited by the appended claims and their equivalents.
Claims
1. A high-strength magnesia-carbon brick preparation process, characterized in that: The steps of the high-strength magnesia carbon brick preparation process are as follows: (1) Proportioning raw materials: Proportioning magnesia particles, flaky graphite, phenolic resin, antioxidant, silicon carbide, alumina, graphite, fly ash, quartz powder, and clay; (2) Processing raw materials: grinding the raw materials into particles of the same size and mixing them; (3) Molding and baking: Molding and baking the mixed raw materials; (4) Final inspection: The finished magnesia carbon bricks are subjected to quality inspection.
2. A high-strength magnesia-carbon brick preparation process according to claim 1, characterized in that: The raw materials are ground into particles of the same size: flake graphite, silicon carbide, aluminum oxide, graphite, fly ash and quartz powder are ground into 120 meshes by a grinder.
3. A high-strength magnesia-carbon brick preparation process according to claim 1, characterized in that: The 50 parts of magnesia particles, 10 parts of flaky graphite, 3 parts of phenolic resin, 5 parts of antioxidant, 5 parts of silicon carbide, 2 parts of aluminum oxide, 5 parts of graphite, 3 parts of fly ash, 8 parts of quartz powder and 9 parts of clay are mixed and stirred in a mixer at 150-300 revolutions per minute for 20-45 minutes.
4. The high-strength magnesia-carbon brick preparation process according to claim 1, characterized in that: The molding and baking process comprises: pressing the mixed magnesia carbon brick raw materials into a mold, and then using a 1200-ton refractory brick molding hydraulic press to press it 10-20 times at 115-200 MPa to form the raw materials. The formed magnesia carbon bricks are sent to a kiln for baking and sintering to obtain finished magnesia carbon bricks.
5. The high-strength magnesia-carbon brick preparation process according to claim 1, characterized in that: The final test includes the hardness test, corrosion resistance test and fire resistance test of magnesia carbon bricks.
6. A high-strength magnesia-carbon brick preparation process according to claim 5, characterized in that: The final test samples are 2 samples for every 100 finished products: (1) Hardness test: Use Rockwell hardness tester to test the hardness of the formed magnesia carbon bricks; (2) Corrosion resistance test: Use a pool with a length of 4-7 meters, a width of 2-5 meters, and a height of 1-3 meters. Divide the pool into two equal parts. Fill one of the pools with salt spray test liquid and the other with citric acid solution. Divide the finished magnesia carbon brick samples into two equal parts, place them in the salt spray test liquid for 8-15 hours, and place them in the citric acid solution for 5-10 hours. (3) Fire resistance test: Place the finished magnesia carbon bricks in a drying furnace at 1500-2000℃ for 30-260 minutes.
7. The high-strength magnesia-carbon brick preparation process according to claim 1, characterized in that: The final inspection: the magnesia carbon brick products after inspection are finely trimmed by a cutting machine and a grinder to obtain the final magnesia carbon bricks.
